2017
DOI: 10.1007/s00107-017-1248-x
|View full text |Cite
|
Sign up to set email alerts
|

Paper-based laminates produced with kraft lignin-rich phenol–formaldehyde resoles meet requirements for outdoor usage

Abstract: Suitability of lignin-phenol-formaldehyde (LPF) resoles was investigated for manufacturing paper-based high-pressure laminates. As lignin source, pine kraft lignin and spruce sodium lignosulfonate were compared, substituting 40 wt% of phenol by lignin in each case. The synthesized resins were characterized for their viscosity development, solid content, pH, free formaldehyde as well as free phenol content and B-time. Paper-based high-pressure laminates were manufactured using the two different resins. The lami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 12 publications
(12 reference statements)
0
9
0
1
Order By: Relevance
“…Consequently, the technological features studied are mainly focused on mechanical strength and hydrolytic stability of the resulting boards. In contrast, impregnation resins are much less well characterized and despite their economic importance only few studies are found focusing on the technological profile important for paper impregnation 29–33 and surface coating 8,23,34–36 . The present article intends to fill this gap to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the technological features studied are mainly focused on mechanical strength and hydrolytic stability of the resulting boards. In contrast, impregnation resins are much less well characterized and despite their economic importance only few studies are found focusing on the technological profile important for paper impregnation 29–33 and surface coating 8,23,34–36 . The present article intends to fill this gap to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the affinity to water depends on the lignin type. Ghorbani et al ., for example, found that the bonding strength of LPF resins using kraft lignin performs better than lignosulphonates under rapid changes in moisture content. This is due to the comparably higher hydrophilicity of lignosulphonates which affiliates to its process‐related salt content …”
Section: Introductionmentioning
confidence: 99%
“…Preparing lignin-phenol-formaldehyde resins substituting 40 wt% of phenol by pine kraft lignin, found good results in plywood improving the water absorption, thickness swelling and mechanical properties like flexural strength, elastic modulus and relative impact energy. 36…”
Section: Resinsmentioning
confidence: 99%